A WD40 Protein Encoding Gene Fvcpc2 Positively Regulates Mushroom Development and Yield in Flammulina velutipes - Wu, Taju; Zhang, Zhenying; Hu, Chengcheng; Zhang, Long; Wei, Shenglong; Li, Shaojie (Frontiers in Microbiology, 2020)
Ascomycota and Basidiomycota are two closely related phyla and fungi in two phyla share some common morphological developmental process during fruiting body formation. In Neurospora crassa, the Gβ-like protein CPC-2 with a seven-WD40 repeat domain was previously reported. By transforming CPC-2 ortholog encoding genes, from 7 different fungal species across Ascomycota and Basidiomycota, into the cpc-2 deletion mutant of N. crassa, we demonstrate that all tested CPC-2 ortholog genes were able to complement the defects of the cpc-2 deletion mutant in sexual development, indicating that CPC-2 proteins from Ascomycota and Basidiomycota have the similar cellular function. Using Flammulina velutipes as a model system for mushroom species, the CPC-2 ortholog FvCPC2 was characterized. Fvcpc2 increased transcription during fruiting body development. Knockdown of Fvcpc2 by RNAi completely impaired fruiting body formation. In three Fvcpc2 knockdown mutants, transcriptional levels of genes encoding adenylate cyclase and protein kinase A catalytic subunit were significantly lower and colony growth became slower than wild type. The addition of cAMP or the PKA-activator 8-Bromo-cAMP into the medium restored the Fvcpc2 knockdown mutants to the wild-type colony growth phenotype, suggesting that the involvement of cAMP production in the regulatory mechanisms of FvCPC2. Knockdown of Fvcpc2 also weakened transcriptional responses to sexual development induction by some genes related to fruiting body development, including 4 jacalin-related lectin encoding genes, 4 hydrophobin encoding genes, and 3 functionally-unknown genes, suggesting the participation of these genes in the mechanisms by which FvCPC2 regulates fruiting body development. All three Fvcpc2 overexpression strains displayed increased mushroom yield and shortened cultivation time compared to wild type, suggesting that Fvcpc2 can be a promising reference gene for Winter Mushroom breeding. Since the orthologs of FvCPC2 were highly conserved and specifically expressed during fruiting body development in different edible mushrooms, genes encoding FvCPC2 orthologs in other mushroom species also have potential application in breeding.